2018
DOI: 10.1038/s41566-018-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Mie resonators for highly directional light emission from monolayer MoS2

Abstract: Controlling light emission from quantum emitters has important applications ranging from solid-state lighting and displays to nanoscale single-photon sources. Optical antennas have emerged as promising tools to achieve such control right at the location of the emitter, without the need for bulky, external optics. Semiconductor nanoantennas are particularly practical for this purpose because simple geometries, such as wires and spheres, support multiple, degenerate optical resonances. Here, we start by modifyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 71 publications
4
151
0
Order By: Relevance
“…This behaviour, that is well-known in highrefractive-index NDs, [49] can be exploited to achieve highly directional scattering when superimposing the MD and ED resonances. [36,37] To shed light on the nature of the observed resonances, we explored the system electrodynamics with the aid of the extended boundary-condition method (EBCM) for the evaluation of the scattering T matrix of nonspherical particles. [50] Since EBCM is based on expanding the incident and scattered fields in spherical waves, the method provides a straightforward way to characterise the resonances in terms of angular-momentum indices, (c) Calculated resonance decomposition for small (150 nm) and large-diameter (250 nm) nanodisks.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour, that is well-known in highrefractive-index NDs, [49] can be exploited to achieve highly directional scattering when superimposing the MD and ED resonances. [36,37] To shed light on the nature of the observed resonances, we explored the system electrodynamics with the aid of the extended boundary-condition method (EBCM) for the evaluation of the scattering T matrix of nonspherical particles. [50] Since EBCM is based on expanding the incident and scattered fields in spherical waves, the method provides a straightforward way to characterise the resonances in terms of angular-momentum indices, (c) Calculated resonance decomposition for small (150 nm) and large-diameter (250 nm) nanodisks.…”
Section: Resultsmentioning
confidence: 99%
“…SiNPs of spherical shape can be fabricated chemically [33] or with fs-laser ablation [34]. In [33], [32], it has been shown that spherical SiNPs and Si nanowires can be placed on 2D TMDCs (WS2 and MoS2, respectively) without damaging their crystalline structure, where an additional thin layer of h-BN can be used for protection or isolation of 2D TNDCs [35].…”
Section: Resultsmentioning
confidence: 99%
“…Spatially complex light fields may still be accessible by constructing metasur-faces from individually directional dielectric nanoantennas or by exploiting coupling between the meta-atoms. A natural future step will also be to combine active control of spontaneous emission [58] with shaping of the spatial emission pattern [39,50] to implement dynamic control of the latter. Also, the possibility to control the polarization of the light emitted by active Mie-resonant nanostructures remains underutilized.…”
Section: Discussionmentioning
confidence: 99%